Pengaruh Kinerja Keuangan terhadap Nilai Perusahaan: - Cahyaningtias, Cindy Eka; Rosyadi, Imron (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This research examines the influence of the variables Current Ratio, Debt to Equity Ratio, and Gross Profit Margin on the value of Automotive and Component Subsector Manufacturing companies listed on the Indonesia Stock Exchange (BEI). The time period covered in this research is 4 (four) years, namely 2019 to 2022. This research uses secondary data, namely collecting information from annual financial reports which include the variables Current Ratio, Debt to Equity Ratio, and Gross Profit. Margins. This data was obtained from 11 samples of companies in the Automotive and Components Subsector Manufacturing sector listed on the Indonesia Stock Exchange (BEI). This research aims to evaluate the influence of these variables on company value. Data processing and analysis methods include descriptive statistical analysis, linear regression on panel data (using the Chow test and Hausman test for selection), multiple linear regression analysis on panel data, hypothesis testing (involving the T test and F test), and data analysis evaluation. coefficient of determination. The results and discussion of the research are that the Current Ratio has a positive but not significant effect on company value, the Debt to Equity Ratio has a negative but not significant effect on company value, and Gross Profit Margin has a positive and significant effect on company value.